Efficacy and safety of intermittent theta-burst stimulation versus continuous theta-burst stimulation for major depressive disorder and bipolar depression: a systematic review - Li, Zhi; Shi, Zhan-Ming; Yang, Xin-Hu; Su, Zhi-Ang; Wei, Wei; Qin, Zhen-Juan; Lan, Xian-Jun; Wei, Xin; Zheng, Wei (Frontiers in Psychiatry, 2026)
BackgroundThe therapeutic efficacy and safety profiles of daily or accelerated intermittent theta-burst stimulation (iTBS) in comparison to daily or accelerated continuous theta-burst stimulation (cTBS) for patients with major depressive disorder (MDD) or bipolar depression (BD) remain inadequately explored, respectively. This systematic review evaluates the efficacy, safety, and tolerability of daily or accelerated iTBS compared to daily or accelerated cTBS in patients with MDD or BD.MethodsA comprehensive search was conducted in both Chinese (WanFang, China National Knowledge Infrastructure) and English (PubMed, EMBASE, PsycINFO, Cochrane Library) databases to identify randomized controlled trials (RCTs) examining the efficacy and safety of daily or accelerated iTBS compared to daily or accelerated cTBS in patients with MDD or BD.ResultsThree studies (n = 87) investigated the efficacy, safety, and tolerability of daily iTBS versus daily cTBS (1 RCT, n = 30) in patients with MDD, and accelerated iTBS versus accelerated cTBS (2 RCTs, n = 57) in patients with MDD or BD. In patients with MDD, daily iTBS outperformed daily cTBS in terms of antidepressant efficacy, with comparable safety and tolerability profiles (1 RCT). Accelerated cTBS demonstrated superior anxiolytic (1 RCT) and anti-suicidal efficacy (1 RCT) compared to accelerated iTBS in MDD, with similar antidepressant efficacy, safety, and tolerability profiles for patients with MDD or BD (2 RCTs).ConclusionAmong the limited number of available studies, the efficacy and safety of daily or accelerated iTBS compared to daily or accelerated cTBS in patients with MDD or BD were uncertain. Future research with larger sample sizes and standardized assessments is essential to confirm these findings.